Pelatihan Pembuatan Lilin Aromaterapi Berbahan Pala dan Cengkih bagi Masyarakat di Negeri Kaitetu - Matulessy, Febby Sonya; Salakory, Hans Sammy Marthin (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Kaitetu village is rich in nutmeg and cloves, but they have not been fully utilised to improve the welfare of the local community. This community service programme in Negeri Kaitetu aims to empower the community through training in making aromatherapy candles from nutmeg and cloves to provide added value to the community. The training method begins with planning, observation, training and evaluation. The result of this training is that participants have knowledge about aromatherapy candles and can make aromatherapy candles. The training was effective in encouraging behaviour change. In addition to providing economic benefits by opening new business opportunities, this programme also provides positive social and environmental impacts. It is hoped that this programme can increase community awareness about the preservation of local spices and the use of natural products, and encourage sustainable economic development in Kaitetu Country.